Role of honey as a bifunctional reducing and capping/stabilizing agent: application for silver and zinc oxide nanoparticles - Bahari, Norfarina; Hashim, Norhashila; Abdan, Khalina; Md Akim, Abdah; Maringgal, Bernard; Al-Shdifat, Laith (Multidisciplinary Digital Publishing Institute, 2023)
The use of natural reducing and capping agents has gained importance as a way to synthesize nanoparticles (NPs) in an environmentally sustainable manner. Increasing numbers of studies have been published on the green synthesis of NPs using natural sources such as bacteria, fungi, and plants. In recent years, the use of honey in the synthesis of metal and metal oxide NPs has become a new and promising area of research. Honey acts as both a stabilizing and reducing agent in the NP synthesis process and serves as a precursor. This review focuses on the use of honey in the synthesis of silver NPs (Ag-NPs) and zinc oxide NPs (ZnO-NPs), emphasizing its role as a reducing and capping agent. Additionally, a comprehensive examination of the bio-based reducing and capping/stabilizing agents used in the honey-mediated biosynthesis mechanism is provided. Finally, the review looks forward to environmentally friendly methods for NP synthesis.